Intervensi Program Bimbingan dan Konseling dalam Mengatasi Bullying Siswa Madrasah Aliyah Negeri Salatiga - Nurlatifah, Andar Ifazatul (IAIN Kudus, 2019)
The Intervention Of Guidance And Counseling Program to Overcome The Bullying Of MAN Salatiga Students. This article a mixed method research with concurrent triangulation design to examine (1) the phenomenon of bullying at MAN Salatiga, (2) the guidance and counseling intervention to deal with bullying at MAN Salatiga, and (3) the ideal guidance and counseling program to overcome bullying at MAN Salatiga. Scale delivered to 157 respondents to measure students’ understanding and involvement in bullying. Interviews with students, guidance and counseling teachers, and FGD followed by lecturers and counselors used to collect information about bullying and bullying intervention. The results of the study revealed that students’ understanding of the concept of bullying is 73.41%, 44.76% students involved in bullying as witness; 34.13% as victim; and 34.25% as bully. There are differences between men and women in understanding of bullying concept and the involvement in bullying. The guidance and counseling teachers’ interventions in dealing with bullying are focused on guidance and counseling responsive services in the form of curative efforts to the victim and bully. Therefore, the ideal program in dealing with bullying is carried out evenly in the frame of guidance and counseling basic services, responsive services, individual planning services, and system support to the victim, the bully, and the witness.